2021
DOI: 10.3389/fpsyg.2021.790727
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Exerted by Time Frames on Consumers’ Willingness to Buy Nearly Expired Food

Abstract: With the development of Internet e-commerce channels, online shopping platforms have become the main channel for consumers to buy nearly expired food. Date labels, as one of the main external clues, play a decisive role in nearly expired food purchasing. Therefore, based on attention-related theory, this study attempts to explore the influence exerted by different time frames on consumers’ willingness to buy and its mechanism. The results show that compared with the date, consumers have a higher willingness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
2
7
0
1
Order By: Relevance
“…They also provided sales promotions like a bulk package or "buy one get one free." These substantial price reduction and sales promotion measures based on the expiration date could greatly trigger consumers to buy impulsively, especially for people with high sensitivity to commodity prices and those with a high preference for price judgment (Song et al, 2021). The study also confirmed the positive and significant effects of utilitarian value on impulse buying, which was in line with previous studies (Zheng et al, 2019;Parsad et al, 2021).…”
Section: Economic Concern Consumer Value Impulse Buying and Food Redu...supporting
confidence: 89%
See 3 more Smart Citations
“…They also provided sales promotions like a bulk package or "buy one get one free." These substantial price reduction and sales promotion measures based on the expiration date could greatly trigger consumers to buy impulsively, especially for people with high sensitivity to commodity prices and those with a high preference for price judgment (Song et al, 2021). The study also confirmed the positive and significant effects of utilitarian value on impulse buying, which was in line with previous studies (Zheng et al, 2019;Parsad et al, 2021).…”
Section: Economic Concern Consumer Value Impulse Buying and Food Redu...supporting
confidence: 89%
“…Therefore, consumers perceive higher food safety risks for advent food since they are approaching the end of shelf-life. Furthermore, the shorter the remaining shelf-life, the higher the perceived food safety risks (Song et al, 2021). Secondly, we can see in our study that environmental concern (b = 0.017, t = 1.644) has a positive and insignificant effect on consumers' waste reduction behaviors.…”
Section: Consumer Concerns and Food Reduction Intentionsupporting
confidence: 50%
See 2 more Smart Citations
“…Date marking can contribute to consumer apprehension of a given food's fitness for consumption (Gong et al, 2022;Connors and Schuelke, 2022). Understanding and interpreting dates impact consumer behaviour, which, in turn, affects consumer purchase and consumption decisions (Tian et al, 2022;Song et al, 2021;Hartmann et al, 2021;Shamim et al, 2021;Kavanaugh and Quinlan, 2020;Thompson et al, 2018;Newsome et al, 2014).…”
Section: Introductionmentioning
confidence: 99%